(untitled) (Journal of the College of Basic Education, 2022)
The Kirkuk Brigade is one of the important Iraqi brigades، occupying an important strategic position in northern Iraq، making it a link between the north and south، As well as rich in resources and natural resources، Most important of all، it is a small Iraq with a colorful social structure composed of different nationalities and sects of Turkmen، Arabs and Kurds، As well as the difference of religions and doctrines in which Muslims، Christ and Jews previously it was natural to make administrative and security changes in the General during the Republican era during the period (1958-1968) and here highlights the importance of research. Department of research on two main subjects، The first topic was entitled (Kirkuk in the first republican era 1958-1963)، which dealt with the most important administrative and security changes that occurred in the Kirkuk Brigade during the reign of Abdul Karim Qasim، The second topic was entitled (The situation of Kirkuk in the second republican era 1963-1968)، which dealt with the administrative and security developments in Kirkuk during the reign of Abdel Salam Aref.